The relationship between quantitative human epidermal growth factor receptor 2 gene expression by the 21-gene reverse transcriptase polymerase chain reaction assay and adjuvant trastuzumab benefit in Alliance N9831. Issue 1 (December 2015) - Perez, Edith; Baehner, Frederick; Butler, Steven; Thompson, E.; Dueck, Amylou; Jamshidian, Farid; Cherbavaz, Diana; Yoshizawa, Carl; Shak, Steven; Kaufman, Peter; Davidson, Nancy; Gralow, Julie; et al.
Abstract Introduction The N9831 trial demonstrated the efficacy of adjuvant trastuzumab for patients with human epidermal growth factor receptor 2 (HER2) locally positive tumors by protein or gene analysis. We used the 21-gene assay to examine the association of quantitative HER2 messenger RNA (mRNA) gene expression and benefit from trastuzumab. Methods N9831 tested the addition of trastuzumab to chemotherapy in stage I–III HER2-positive breast cancer. For two of the arms of the trial, doxorubicin and cyclophosphamide followed by paclitaxel (AC-T) and doxorubicin and cyclophosphamide followed by paclitaxel and trastuzumab concurrent chemotherapy-trastuzumab (AC-TH), recurrence score (RS) and HER2 mRNA expression were determined by the 21-gene assay (Oncotype DX®) (negative <10.7, equivocal 10.7 to <11.5, and positive ≥11.5 log2 expression units). Cox regression was used to assess the association of HER2 expression with trastuzumab benefit in preventing distant recurrence. Results Median follow-up was 7.4 years. Of 1, 940 total patients, 901 had consent and sufficient tissue. HER2 by reverse transcriptase polymerase chain reaction (RT-PCR) was negative in 130 (14 %), equivocal in 85 (9 %), and positive in 686 (76 %) patients. Concordance between HER2 assessments was 95 % for RT-PCR versus central immunohistochemistry (IHC) (>10 % positive cells = positive), 91 % for RT-PCR versus central fluorescence in situ hybridization (FISH) (≥2.0 = positive) and 94 % for central IHC versus central FISH. In the primary analysis, the association of HER2 expression by 21-gene assay with trastuzumab benefit was marginally nonsignificant (nonlinearp = 0.057). In hormone receptor-positive patients (local IHC) the association was significant (p = 0.002). The association was nonlinear with the greatest estimated benefit at lower and higher HER2 expression levels. Conclusions Concordance among HER2 assessments by central IHC, FISH, and RT-PCR were similar and high. Association of HER2 mRNA expression with trastuzumab benefit as measured by time to distant recurrence was nonsignificant. A consistent benefit of trastuzumab irrespective of mHER2 levels was observed in patients with either IHC-positive or FISH-positive tumors. Trend for benefit was observed also for the small groups of patients with negative results by any or all of the central assays. Trial registration Clinicaltrials.govNCT00005970 . Registered 5 July 2000.